2009
DOI: 10.1007/978-3-642-00477-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Medical Implants

Abstract: Drug-eluting medical implants are actually active implants that induce healing effects, in addition to their regular task of support. This effect is achieved by controlled release of active pharmaceutical ingredients (API) into the surrounding tissue. In this chapter we focus on three types of drug-eluting devices: drug-eluting vascular stents, drug-eluting wound dressings and protein-eluting scaffolds for tissue regeneration, thus describing both internal and external implants. Each of these drug-eluting devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 139 publications
0
24
0
1
Order By: Relevance
“…The study showed that the coating was depleted for chlorhexidine after two and tetracycline after seven days , respectively. Xing et al [27] analyzed the antibacterial effect of doxycycline-coated dental abutments and observed reduced biofilm formation on the functionalized surfaces. Similar to the the results of our study, a high drug-load was essential for keeping up antibacterial activity over a prolonged period of time.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that the coating was depleted for chlorhexidine after two and tetracycline after seven days , respectively. Xing et al [27] analyzed the antibacterial effect of doxycycline-coated dental abutments and observed reduced biofilm formation on the functionalized surfaces. Similar to the the results of our study, a high drug-load was essential for keeping up antibacterial activity over a prolonged period of time.…”
Section: Discussionmentioning
confidence: 99%
“…These functionalized surfaces may contain elements of the extracellular matrix, ceramics, ions or 292 F. Witte et al synthetic polymers responsible for an enhanced osseointegration, especially for improving the adhesion of osteoblasts [47][48][49], bioactive proteins which serve as growth factors [50,51], antiinflammatory proteins [52] or antimicrobial substances to prevent biofilm production [53,54].…”
Section: Musculoskeletal Biohybridsmentioning
confidence: 99%
“…The desired outcome when cells are exposed to the pDNA packets is for each cell to direct the pDNAs to the cell nucleus and produce the protein in relevant levels for applications in gene therapeutics [61], [62], diagnostics and functional genomics [63], [64], medical devices [65], and tissue engineering [66], [67]. However, the primary transmission as described (Fig.…”
Section: Primary Transmission Lossesmentioning
confidence: 99%